2010
DOI: 10.1143/jpsj.79.024706
|View full text |Cite
|
Sign up to set email alerts
|

Environment Effects on Excitons in Semiconducting Carbon Nanotubes

Abstract: Effects of environmental dielectric screening on excitons in carbon nanotubes are studied within a k Á p scheme and a continuum model. They are shown to be sensitive to the effective distance between the nanotube and the dielectric medium relative to the diameter. For material surrounding the nanotube, the band gap decreases with the increase of the dielectric constant, but the energy of the ground exciton exhibits only a slight decrease for effective distance comparable to interlayer spacing of bulk graphite.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 80 publications
5
54
0
Order By: Relevance
“…Previous calculations for parallel polarization show that the exciton energy is almost independent of (e 2 /κL)/(2πγ /L) between 0.1, corresponding to κ ≈ 4, and 0.2, corresponding to κ ≈ 2, for both first and second gaps. 6,19 For cross polarization, the exciton energy is more sensitive to the interaction parameter, suggesting 0. …”
Section: Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous calculations for parallel polarization show that the exciton energy is almost independent of (e 2 /κL)/(2πγ /L) between 0.1, corresponding to κ ≈ 4, and 0.2, corresponding to κ ≈ 2, for both first and second gaps. 6,19 For cross polarization, the exciton energy is more sensitive to the interaction parameter, suggesting 0. …”
Section: Formulationmentioning
confidence: 99%
“…13 In experiments, the photoluminescence studies 14,15 of double-wall nanotubes have reported that the energies of the optically active exciton states of the inner tubes are redshifted from those of single-wall tubes with the same chiral indices, where the effective dielectric screening is expected to be modified by the presence of the surrounding outer tube, i.e., environmental effects. [16][17][18][19] Double-wall tubes are the simplest systems of multiwall carbon nanotubes and thus are suited for studying the interactions between different walls. [20][21][22][23][24][25][26][27][28] In this work we examine effects of screening by the interwall Coulomb interaction on excitons and optical spectra in double-wall tubes based on the effective-mass theory and a static screened Hartree-Fock approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the dielectric functions (39) and (40) are closely related to that in the presence of environmental dielectric material surrounding or inserted into a single-wall nanotube, respectively. 18,65,66 The correspondence is discussed in Appendix B.…”
Section: Double-wall Tubesmentioning
confidence: 99%
“…5,18 However, the exciton energy in cross-polarization geometry restricts the interaction parameter, suggesting 0.…”
Section: Double-wall Tubesmentioning
confidence: 99%
See 1 more Smart Citation